Bachelor of education in service teacher trainees’ perceptions and attitudes on inclusive education in Zimbabwe - Mandina, Shadreck (Canadian Center of Science and Education, 2021)
The purpose of this study was to investigate inclusion and the perceptions and attitudes that Bachelor of Education in service trainee teachers hold towards inclusive education in Zimbabwe. The participants were 97 main stream in-service Bachelor of Education teacher trainees (43 male, 54 female) from Midlands State University’s Faculty of Education. The research design was exploratory and descriptive in nature. A questionnaire was used for data collection. The findings indicate that main stream trainee teachers believe that children with severe disabilities would benefit from being in an inclusion class however the main stream teachers feel that their college training is not sufficient enough to equip them to teach in an inclusion setting, especially those children with severe disabilities and emotional and behavioral problems. The findings also indicate that main stream trainee teachers in Zimbabwe have somewhat negative attitudes towards inclusive education. The teachers noted that large class sizes, inadequate resources and facilities and lack of support as challenges militating against the implementation of inclusive education. Recommendations on the improvement of inclusive education in Zimbabwe especially on the need for increased support from the government and the private and public sector in terms of funding to purchase equipment and resource facilities as well as upgrading of infrastructure and teacher training to make inclusive education a success in Zimbabwe were made.